Crystal structure of bis[benzyl(methyl)carbamodithioato-κ2S,S′]-di-n-butyltin(IV), C26H38N2S4Sn - Nurul Amalina, Abd Aziz; Normah Awang,; Chan, Kok Meng; Nurul Farahana Kamaludin,; Nur Naj, Mohamad Anuar; Nur Atiyah, Nadhrah Jamaludin; Tan, Yee Seng *; Tiekink, Edward R. T. * (De Gruyter, 2023)
C26H38N2S4Sn, triclinic, P 1 ‾ (no. 2), a = 9.6272(1) Å, b = 12.1043(2) Å, c = 13.3584(2) Å, α = 82.296(1)°, β = 86.611(1)°, γ = 66.912(1)°, V = 1419.02(4) Å3, Z = 2, Rgt (F) = 0.0235, wR ref(F 2) = 0.0612, T = 100 K.